Pentoxifylline inhibits the fibrogenic activity of pleural effusions and transforming growth factor-β - P. Entzian; M. Schlaak; U. Seitzer; Y. Acil; M. Ernst; P. Zabel (Mediators of Inflammation)
Physiopathology of organ fibrosis is far from being completely understood, and the efficacy of the available therapeutic strategies is disappointing. We chose pleural disease for further studies and addressed the questions of which cytokines are relevant in pleural fibrosis and which drugs might interrupt its development. We screened pleural effusions for mediators thought to interfere with fibrogenesis (transforming growth factor-β (TGF-β), tumour necrosis factor α (TNFα), soluble TNF-receptor p55 (sTNF-R)) and correlated the results with patient clinical outcome in terms of extent of pleural thickenings. We found pleural thickenings correlated with TGF-β (p<0.005) whereas no correlations could be observed with TNFα and sTNF-R. Further, we were interested in finding out how TGF-β effects on fibroblast growth could be modulated. We found that pentoxifylline is able to inhibit both fibroblast proliferation and collagen synthesis independently of the stimulus. We conclude that, judging from in vitro studies, pentoxifylline might offer a new approach in the therapy of pleural as well as pulmonary fibrosis.